"Settlor-ing" their differences: protector or protagonist?. Issue 8 (20th July 2022) - Leung, Samuel Yee Ching; Au-Yeung, Bennett
Abstract: It is not common to see offshore jurisdictions adopting polarised jurisprudence. The conflict between The X Trusts [2021] SC (Bda) 72 Civ and In the matter of The Piedmont Trust and the Riviera Trust [2021] JRC 248 is such a rare occasion. The dispute concerning whether the scope of a protector's powers should be wide or narrow had, apart from putting the jurisdictions at a crossroad, also aptly put the protagonist trustee in a contest for screen time with the tritagonist protector. In solving this challenge, we venture to take on a fresh perspective in suggesting that the scope of a protector's power should be determined by ascertaining the intention of a settlor in light of all the relevant circumstances of a particular trust. Towards the end of this article, we also make some observations for settlors and practitioners from a practical point of view.